The Methanol Extract of Polygonatum odoratum Ameliorates Colitis by Improving Intestinal Short-Chain Fatty Acids and Gas Production to Regulate Microbiota Dysbiosis in Mice - Ye, Xuewei; Pi, Xionge; Zheng, Wenxin; Cen, Yingxin; Ni, Jiahui; Xu, Langyu; Wu, Kefei; Liu, Wei; Li, Lanjuan (Frontiers in Nutrition, 2022)
The potential impacts of methanol extract from Polygonatum odoratumon(YZM) colonic histopathology, gut gas production, short chain fatty acids (SCFAs) and intestinal microbiota composition were evaluated with dextran sulfate sodium (DSS)-induced colitis mice in this study. These results indicated that YZM increased colon length, ameliorated colonic histopathology in DSS-induced colitis mice. Moreover, YZM administration obviously reversed the compositions of intestinal microbiota leading to the inhibition of H2S-related bacteria (e.g., Desulfovibrionaceae) along with the lower level of H2S, as well as higher contents of SCFAs-related bacteria (e.g., Muribaculaceae). Taken together, the effects of methanol extract from Polygonatum odoratum is studied to provide new enlightenment and clues for the application as functional food and clinical drug. Our study first revealed the relationship between intestinal gas production and key bacteria in ulcerative colitis.